Does surgery affect systemic immune response? a perioperative analysis of TGF-β, IL-8 and CD45RO - Trumet, Leah; Ries, Jutta; Ivenz, Niclas; Sobl, Philip; Wehrhan, Falk; Lutz, Rainer; Kesting, Marco; Weber, Manuel (Frontiers in Oncology, 2023)
The options of (neo-)adjuvant immunotherapy in addition to surgery in the treatment of oral squamous cell carcinoma (OSCC) are steadily increasing, but patients do not always respond to therapy as intended. The objectives of this study were to investigate the systemic perioperative course of the biomarkers CD45RO, TGF-β, and IL-8 in non-tumor-related minor and tumor-related major maxillofacial surgery and to perform association analyses with demographic and histomorphologic parameters. A deeper understanding of surgery-related changes in various of different immune biomarkers could help to better understand the immunologic consequences of surgery which could influence immunotherapeutic protocols.Peripheral whole blood from 38 patients was analyzed by real-time quantitative polymerase chain reaction (RT-qPCR) at five different timepoints before and after maxillofacial surgery to detect changes in mRNA expression of the biomarkers TGF-β, IL-8 and CD45RO. All patients underwent general anesthesia to undergo either resection and free flap reconstruction for OSCC or minor maxillofacial surgery (controls). Statistical analysis was done using Mann-Whitney-U test, Wilcoxon test, and Spearman's correlation.Compared to the preoperative expression, there was a significant postoperative downregulation of CD45RO, TGF-β and IL-8 until the 4th postoperative day (p≤0.003) in OSCC patients. For TGF-β and IL-8, the reduction in expression was significant (p≤0.004) compared to controls. By postoperative day 10, all analyzed parameters converged to baseline levels.Only CD45RO still showed a significant downregulation (p=0.024). Spearman analysis revealed a significant correlation between increased duration of surgery and perioperative reduction in peripheral blood expression of CD45RO, TGF-β and IL-8 (p≤0.004). Perioperative changes in TGF-β and PD-L1 expression were shown to be not correlated. Preoperative TGF-β expression was significantly lower in patients with lymph node metastases (p=0.014).